Wealth Transfers and Tax Planning: Evidence for the German Bequest Tax - Eric Sommer (Institute of Labor Economics (IZA), 2017)
The rising importance of bequests as a source of personal income lead to renewed interest in the taxation of wealth transfers. Empirical evidence on distortionary effects of bequest taxation is relatively scarce. On the basis of administrative data for Germany, this paper assesses the extent to which taxable bequests are targeted to the tax code. I investigate bunching at discrete jumps in the marginal tax rate. While there is evidence for tax planning in case of inter-vivo gifts, inheritances do not exhibit bunching. Further heterogeneity analyses demonstrate that tax planning is highest for gifts between close relatives. While the overall tax base responsiveness is rather low, the findings suggest that bequest tax planning almost exclusively occurs for donors rather than recipients of wealth transfers. Beyond, tax planning is more prevalent for close relatives and large estates.
Keywords: D91; H26; H31; 330; bequest tax; tax planning; bunching; administrative data